OPTIMISING ONLINE AND HYBRID LEARNING TO IMPROVE THE QUALITY OF EDUCATION AND STUDENT LEARNING EXPERIENCES: A LITERATURE REVIEW ANALYSIS IN THE CONTEXT OF THE MODERN DIGITAL EDUCATION ENVIRONMENT - Moh. Imron Rosidi; Novianti Sisilia (Indonesian Journal of Education (INJOE), 2025)
This article presents an analysis of the optimisation of online and hybrid learning to improve the quality of education and student learning experiences in the context of a modern digital education environment. The research uses a literature review method. The results show that the hybrid learning model has great potential in combining the advantages of face-to-face and online learning, thereby creating a more humanistic, flexible, and student-centred learning experience. The integration of appropriate pedagogical approaches and the planned use of digital technology can support the achievement of better education quality and build a sustainable learning ecosystem. This study recommends strengthening the capacity of educators, developing policies that support digital transformation, and conducting further testing in diverse empirical contexts to refine the model for optimising online and hybrid learning.